Pattumateang: The History of Death Traditions in Cikoang Village, Takalar Regency - Nur Sani; Najamuddin Najamuddin; M. Rasyid Ridha; Bakhtiar Bakhtiar (MASI Mandiri Edukasi, 2026)
The Pattumateang death tradition in Cikoang Village, Takalar Regency, represents a cultural practice that emerged from a long historical process of acculturation between Islamic teachings and the local customs of the Bugis-Makassar community. This study aims to examine the historical origins of Pattumateang, analyze its forms of cultural acculturation, and explore its continuity as a living tradition into the 21st century. This research employs a historical-anthropological approach using qualitative methods, including heuristic data collection, source criticism, interpretation, and historiography. Data were gathered through in-depth interviews, field observations, and documentation and literature studies. The findings reveal that Pattumateang developed alongside the Islamization of Cikoang since the 17th century through dialogical and accommodative da’wah strategies. The tradition functions not only as a mortuary ritual but also as a social institution that strengthens solidarity, community cohesion, and the intergenerational transmission of religious and cultural values. Amid contemporary social changes, Pattumateang demonstrates adaptive characteristics as a living tradition, capable of adjusting its practices without losing its core meaning. This study contributes to understanding local Islam as a dynamic cultural process shaped through continuous negotiation between religious doctrines and local traditions. It also enriches the discourse on historical anthropology by highlighting how cultural practices persist, transform, and remain relevant across changing social contexts.